Reliability and Factorial Validity of the Turkish Version of the Pain Disability Index in Rheumatic Patients With Chronic Pain - Mustafa UĞURLU; Görkem Karakaş UĞURLU; Şükran ERTEN; Semra ULUSOY KAYMAK; Ali ÇAYKÖYLÜ (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate the reliability, factor structure, and validity of the Turkish version of the Pain Disability Index (PDI) in patients with chronic pain. Patients and methods: The PDI Index was translated into Turkish according to the standard procedures and performed on 212 rheumatic patients with chronic pain (34 males, 178 females; mean age 47.9±10.3 years; range 19 to 65 years), with most common diagnoses including rheumatoid arthritis, seronegative spondyloarthropathies, and familial Mediterranean fever. Exploratory and confirmatory factor analyses were used for validation and Cronbach’s alpha coefficient was determined as the internal reliability of the PDI. Correlations between each item and item-total score were also calculated. Results: The Turkish form of the PDI revealed a two-factor model. Cronbach’s alpha for the total scale was found as 0.86. All items were correlated significantly with the total score, with values ranging from 0.73 to 0.81. An analysis of the confirmatory factor revealed that the model fit was adequate. Conclusion: The Turkish version of PDI had adequate psychometric properties in rheumatic patients with chronic pain. Thus, it may be useful in clinical practice to assist in better understanding of diseases characterized by chronic pain, providing objective measures for functional deficits, and monitoring treatment or rehabilitation effects.